Commercialization of selected forage innovations - Gebreyes, Million; Mekonnen, Kindu; Bezabih, Melkamu; Assefa, Getnet; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Refresher Training Workshop on Feeds, Forage for Dairy Development, Addis Ababa, 27-28 March 2023